Environmental sustainability in endodontics. A life cycle assessment (LCA) of a root canal treatment procedure - Brett Duane; Linnea Borglin; Stephanie Pekarski; Sophie Saget; Henry Fergus Duncan (BMC, 2020)
Abstract Background To analyse via life cycle analysis (LCA) the global resource use and environmental output of the endodontic procedure. Methodology An LCA was conducted to measure the life cycle of a standard/routine two-visit RCT. The LCA was conducted according to the International Organization of Standardization guidelines; ISO 14040:2006. All clinical elements of an endodontic treatment (RCT) were input into OpenLCA software using process and flows from the ecoinvent database. Travel to and from the dental clinic was not included. Environmental outputs included abiotic depletion, acidification, freshwater ecotoxicity/eutrophication, human toxicity, cancer/non cancer effects, ionizing radiation, global warming, marine eutrophication, ozone depletion, photochemical ozone formation and terrestrial eutrophication. Results An RCT procedure contributes 4.9 kg of carbon dioxide equivalent (CO2 eq) emissions. This is the equivalent of a 30 km drive in a small car. The main 5 contributors were dental clothing followed by surface disinfection (isopropanol), disposable bib (paper and plastic), single-use stainless steel instruments and electricity use. Although this LCA has illustrated the effect endodontic treatment has on the environment, there are a number of limitations that may influence the validity of the results. Conclusions The endodontic team need to consider how they can reduce the environmental burden of endodontic care. One immediate area of focus might be to consider alternatives to isopropyl alcohol, and look at paper, single use instrument and electricity use. Longer term, research into environmentally-friendly medicaments should continue to investigate the replacement of current cytotoxic gold standards with possible natural alternatives. Minimally invasive regenerative endodontics techniques designed to stimulate repair or regeneration of damaged pulp tissue may also be one way of improving the environmental impact of an RCT.